Microglial Activation in the Pathogenesis of Huntington’s Disease - Yang, Hui-Ming; Yang, Su; Huang, Shan-Shan; Tang, Bei-Sha; Guo, Ji-Feng (Frontiers in Aging Neuroscience, 2017)
Huntington’s disease (HD) is an autosomal dominantly inherited neurodegenerative disorder caused by expanded CAG trinucleotide repeats (> 36) in exon 1 of HTT gene that encodes huntingtin protein. Although HD is characterized by a predominant loss of neurons in the striatum and cortex, previous studies point to a critical role of aberrant accumulation of mutant huntingtin in microglia that contributes to the progressive neurodegeneration in HD, through both cell-autonomous and non-cell-autonomous mechanisms. Microglia are resident immune cells in the central nervous system (CNS), which function to surveil the microenvironment at a quiescent state. In response to various pro-inflammatory stimuli, microglia become activated and undergo two separate phases (M1 and M2 phenotype), which release pro-inflammmatory cytokines (IL-1β, IL-6 and TNF-α), anti-inflammatory cytokines, and growth factors (TGF-β, CD206 and Arg1), respectively. Immunoregulation by microglial activation could be either neurotoxic or neuroprotective. In this review, we summarized current understanding about microglial activation in the pathogenesis and progression of HD, with a primary focus of M1 and M2 phenotype of activated microglia and their corresponding signaling pathways.